ANALISIS KUALITAS AUDIT TERHADAP MANAJEMEN LABA AKUNTANSI: STUDI PENDEKATAN COMPOSITE MEASURE VERSUS CONVENTIONAL MEASURE - Herusetya, Antonius (Jurnal Akuntansi dan Keuangan Indonesia, 2012)
This study investigates the effect of audit quality on earnings management behavior using a variety of audit quality proxies, either using a single proxy or a joint test of some proxies of audit quality. The study proposed a new composite measure of audit quality called the Audit Quality Metric Score (AQMS), which represents the dimension of competence and independence of audit quality. The study compared the validity of the conventional and the multidimensional measurement of audit quality. With a sample of 1,152 firm-years panel data of non-financial companies listed in the Indonesia Stock Exchange (IDX) for the year 1999-2007, the study found a negative effect of audit quality over the accrual earnings management, whether using conventional or multidimensional measures of audit quality. These findings are consistent with the previous findings. The study did not find evidence that composite measure of audit quality has higher validity than conventional measures. Rather, we found evidence that Big 4 as a single proxy of audit quality has higher validity compared to the other proxies or using AQMS. The findings of this study are robust due to sensitivity test that support the main findings.